Social Responsibility of the Members of the UPDAA Facebook Group/John Deuter M. Figueroa. - Figueroa, Deuter M
INTRODUCTION: The high prevalence of dental diseases, workforce shortage and maldistribution, and expensive services suggest that individual treatment may be inadequate to alleviate the oral disease burden in the Philippines. Hence, it calls for social responsibility in dentistry. Social responsibility is the commitment to do something beneficial for the public beyond legal and economic obligations. The study aims to identify and describe the socially responsible activities/behaviors in the practice of dentists on the UP Dental Alumni (UPDAA) Facebook Group.